Religion and Morality
XIX, 355 p.
Keywords: Reflection on religion inevitably involves consideration of its relation to morality. When great evil is done to human beings, we may feel that something absolute has been violated. Can that sense, which is related to gratitude for existence, be expressed without religious concepts? Can we express central religious concerns, such as losing the self, while abandoning any religious metaphysic? Is moral obligation itself dependent on divine commands if it is to be objective, or is morality not only independent of religion, but its accuser if God is said to allow horrendous evils? In any case, what happens to the absolute claims of religion in what is, undeniably, a morally pluralistic world? These are the central questions discussed by philosophers of religion and moral philosophers in this collection. They do so in ways which bring new aspects to bear on these traditional issues.